A Survey of Prescription Errors in Paediatric Outpatients in Multi-Primary Care Settings: The Implementation of an Electronic Pre-Prescription System - Tan, Lu; Chen, Wenying; He, Binghong; Zhu, Jiangwei; Cen, Xiaolin; Feng, Huancun (Frontiers in Pediatrics, 2022)
Background: Prescription errors impact the safety and efficacy of the therapy. A higher rate has been considered for pediatric populations. Nevertheless, prescribing information in pediatrics is still lacking, particularly under primary care settings. A need therefore exists to describe the prevalence and characteristics of prescription errors in paediatric outpatients with the aim of improving the preventability during the prescription stage. Methods: A retrospective study of a sample of paediatric outpatients, medication prescriptions after an electronic pre-prescription system implementation were performed in multi-primary care settings between August 2019 and July 2021. Confirmed errors in the prescriptions were automatically reviewed by system and then potentially inappropriate prescriptions would be analyzed by remote pharmacists after electronic transmission. Demographics of pediatric patients, prescription details and types/rates of errors were assessed. Results: A total of 39,754 outpatient pediatric prescriptions in 13 community health care centres were reviewed, among of which 1724 of prescriptions (4.3%) were recruited in the study as they were recognized as valid paediatric prescriptions. Dose errors were the most prevalent (27.0%), with predominance of underdosing (69.0 %). There were followed by errors in selection without specified indications (24.5%), incompatibility (12.4%) and frequency errors (9.9%). Among the critical errors were the drug duplication (8.7%), contraindication (0.9%) and drug interaction (0.8%) that directly affect the drug’s safety and efficacy. Notably, error rates were highest in medications for respiratory system drugs (50.5%), antibiotics (27.3%) and Chinese traditional medicine (12.3%). Conclusion: Our study provides the prevalence and characteristics of prescription errors of paediatric outpatients in community settings based on an electronic pre-prescription system. Dose calculations and medications commonly prescribed in primary-care settings, such as respiratory system drugs, antibiotics and Chinese traditional medicine, are certainly to be aware of. These results highlight an essential requirement to update the rules of prescriptions in the pre-prescription system to facilitate delivery of excellent therapeutic outcomes.